Sign in

Sign up

Answered by **Report**

Y = 2x+5y = 6x+1Just substitute. y = 2x+56x+1 = 2x+56x-2x = 5-14x = 4x = 1Then, insert x = 1 into one of the equation. Let's say I choose number one.y = 2x+5y = 2(1) + 5y = 7

Answered by **vivindalka**

Y=2x+5y=6x+1y=2x+52x+5=6x+1y=2x+52x-6x=1-5y=2x+5-4x=-4 / : (-4)y=2x+5x=1x=1y=2*1+5x=1y=2+5x=1y=7

Didn't find the right answer?

Use site search If you are not satisfied with the answer. Or browse Mathematics category to find out more.

Ask Your Question

Questions without answers